CROSSCULTURAL UNDERSTANDING STRATEGY IN SPEAKING LESSON TO OVERCOMING SPEAKING ANXIETY - Anggraeni, Anita; Rachmijati, Cynantia (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
The students are generally inseparable from liking popular culture to become a fan Â and finally become their identity. In addition to favoring Western culture, there have also been other great cultures lately, for example Japanese, Korea, Thailand and so on. This study aims to examine whether with cross cultural knowledge students are expected to be more confident in speaking and reducing talking anxiety. This research method is descriptive qualitative research method. The data in this study were obtained from interviews and questionnaires adapted from Horwitzs